2006
DOI: 10.1007/s00464-005-3008-y
|View full text |Cite
|
Sign up to set email alerts
|

The MISTELS program to measure technical skill in laparoscopic surgery

Abstract: The MISTELS metrics have excellent reliability, which exceeds the threshold level of 0.8 required for high-stakes evaluations. These findings support the use of MISTELS for evaluation in many different settings, including residency training programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
119
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(126 citation statements)
references
References 11 publications
0
119
0
7
Order By: Relevance
“…The training and accreditation program FLS only takes into account parameters such as completion time and procedural performance (accuracy error) for evaluation purposes (19,20). However, to better understand surgical gestures and to exploit the possibilities that can offer tracking technologies, a wider range of metrics should be considered and analysed (see Table IV).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The training and accreditation program FLS only takes into account parameters such as completion time and procedural performance (accuracy error) for evaluation purposes (19,20). However, to better understand surgical gestures and to exploit the possibilities that can offer tracking technologies, a wider range of metrics should be considered and analysed (see Table IV).…”
Section: Discussionmentioning
confidence: 99%
“…This program consists of web-based study guides and hands-on manual skills practice and training. The manual skills assessment is based on the McGill Inanimate System for Training and Evaluation of Laparoscopic Skills (MISTELS), which consists of a series of five tasks with an objective scoring system (20). It uses time and accuracy (number of errors) in order to assess each individual task.…”
Section: Scoring Systemsmentioning
confidence: 99%
“…To shorten learning curves and to reduce accidents and complications, specific LPS and some typical surgical skills, such as suturing or knot tying, must be learnt outside the OR. Although several training devices and methods for laparoscopic skills acquisition have been reported [7][8][9][10][11][12][13][14], most studies focused on models that recreate operative conditions and very few on the specific LPS. Virtual reality models have been proposed in this regard but, as they are still very expensive, a simple and broad implementation (not only at specialised centres) is not feasible today.…”
Section: Discussionmentioning
confidence: 99%
“…48 The MISTELS system was designed to objectively assess basic laparoscopic skills through a series of structured tasks performed under video guidance in a box trainer. 49,50 MISTELS has been shown to discriminate between competent and non-competent laparoscopic surgeons and may be used to evaluate individual skill levels. 51 These box trainers have been studied and validated extensively and have progressed into the Fundamentals of Laparoscopic Surgery training course and evaluation system (FLS).…”
Section: Box Trainersmentioning
confidence: 99%
“…55 The MISTELS is used within the FLS to assess technical skill. 50,56 The FLS exams are only available to a few centers in the United States and Canada. Consequently participation In numerous studies, the FLS program has been found to be a valid teaching and assessment tool for laparoscopic knowledge and skills.…”
Section: 36mentioning
confidence: 99%